LABORATORY SCALE OF RAYON FIBER MANUFACTURING: MANUAL STIRRING AND STIRRING USING A MAGNETIC STIRRER - Dewi Nurhidayati; Warmiati; Wijayanti (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2024)
Laboratory scale production of rayon fiber has been carried out using manual stirring and a magnetic stirrer. The aim of this research is to compare rayon fiers produced through manual stirring and magnetic stirrer stirring. Experiments on making rayon on a laboratory scale are carried out for educational purposes which often have obstacles due to the limited availability of mixing equipment, such as magnetic stirrer. The method used in making rayon in this research is through the formation of cuprammonium ions. The results show that there is no significant difference between rayon produced manual stirring and magnetic stirrer stirring. It means that the manual mixing can be applied in the learning process for making rayon due in order to get around the limitations of available mixing equipments.